Application of Humanistic Learning Theory in Islamic Religious Education Subjects at SMK 1 Sleman - Hakim, Muh Luqmanul; Aulia, Ridha; Musaddad, Anwar; Putra, Syawal Kurnia; Siregar, Wanidi (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
The purpose of the article is to examine the implementation of humanistic values in Islamic Religious Education (PAI) at the Yayasan Pembina Generasi Muda 1 Vocational High School in Sleman, Yogyakarta. Using a qualitative case study approach, this study involved five key informants, including three teachers and two students. Data collection was conducted for two weeks, from May 5, 2024, through in-depth interviews, participatory observation, and documentation. Data analysis was carried out in four steps: data collection, data condensation, data display, and conclusion. The study findings show that PAI teachers have systematically implemented the humanistic learning approach through adaptive lesson design, varied methods, and provided students with space for expression and freedom in learning. Teachers act as facilitators and motivators. At the same time, students are encouraged to be more active and reflective in the learning process. The compatibility between the Merdeka Curriculum and Islamic values supports the implementation of the humanistic learning approach. These findings contribute to enriching the literature on humanistic-based PAI learning practices in the context of vocational schools. Additionally, this study provides practical insights for educators and policymakers to develop a more participatory, inclusive, and holistic student potential development-oriented PAI learning model.